Leakiness of Pinned Neighboring Surface Nanobubbles Induced by Strong Gas–Surface Interaction - Maheshwari, Shantanu (ACS Nano, 2018)
[Image: see text] The stability of two neighboring surface nanobubbles on a chemically heterogeneous surface is studied by molecular dynamics (MD) simulations of binary mixtures consisting of Lennard-Jones (LJ) particles. A diffusion equation-based stability analysis suggests that two nanobubbles sitting next to each other remain stable, provided the contact line is pinned, and that their radii of curvature are equal. However, many experimental observations seem to suggest some long-term kind of ripening or shrinking of the surface nanobubbles. In our MD simulations we find that the growth/dissolution of the nanobubbles can occur due to the transfer of gas particles from one nanobubble to another along the solid substrate. That is, if the interaction between the gas and the solid is strong enough, the solid–liquid interface can allow for the existence of a “tunnel” which connects the liquid–gas interfaces of the two nanobubbles to destabilize the system. The crucial role of the gas–solid interaction energy is a nanoscopic element that hitherto has not been considered in any macroscopic theory of surface nanobubbles and may help to explain experimental observations of the long-term ripening.